2000
DOI: 10.1046/j.1432-1327.2000.01251.x
|View full text |Cite
|
Sign up to set email alerts
|

Antitermination in bacteriophage λ

Abstract: The solution structure of a 15-mer nutRboxB RNA hairpin complexed with the 36-mer N-terminal peptide of the N protein (N36) from bacteriophage lambda was determined by 2D and 3D homonuclear and heteronuclear magnetic resonance spectroscopy. These 36 amino acids include the arginine-rich motif of the N protein involved in transcriptional antitermination of phage lambda. Upon complex formation with boxB RNA, the synthetic N36 peptide binds tightly to the major groove of the boxB hairpin through hydrophobic and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 68 publications
(98 reference statements)
3
64
0
Order By: Relevance
“…5, we show the biological in vivo activity and the amplitude of the ultrafast component for WT, KH, and ER. The stacking of (Upper) Stacked structure is a schematic representation of the WT complex from NMR studies (10,11). Domain motion of the C-terminal portion of N peptides switches the stacked structure to the unstacked structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5, we show the biological in vivo activity and the amplitude of the ultrafast component for WT, KH, and ER. The stacking of (Upper) Stacked structure is a schematic representation of the WT complex from NMR studies (10,11). Domain motion of the C-terminal portion of N peptides switches the stacked structure to the unstacked structure.…”
Section: Discussionmentioning
confidence: 99%
“…NMR structural studies (10)(11)(12) demonstrated that the amino terminal of the N protein (N peptide), which features an arginine-rich motif, binds to the boxB RNA hairpin as a bent ␣-helix, and this process enforces the purine-rich boxB RNA pentaloop to adopt a canonical GNRA fold (13,14) with the fourth purine residue extruded (Fig. 1).…”
mentioning
confidence: 99%
“…Alternatively, the affinity purification tag can be separated from the protein of interest. In the case of small peptides, removal of the affinity purification tag was often achieved using cyanogen bromide that specifically hydrolyzes peptide bonds C-terminal of methionines [7,9,15,16,19,33,42,44]. In the case of protein domains that often contain internal methionines, other methods for cleavage are generally used and involve specific proteases.…”
Section: Purification Of Rna Binding Proteinsmentioning
confidence: 99%
“…For example single 15 N [Gly] labels were introduced into a 14-residue peptide to facilitate the assignments of three glycine residues [31]. However, bacterial expression is also frequently used to generate uniform 15 N or 15 N/ 13 C labeled peptides [6,7,9,19,33,42,44,165].…”
Section: Typical Samples For Nmr Measurements Of Peptide-rna Complexesmentioning
confidence: 99%
See 1 more Smart Citation